Daya Tarik Wisata dan Promosi Instagram Yang Memengaruhi Keputusan Berkunjung Wisatawan di The Ranch Cisarua - Muhammad Rifki Alian; Mariana R. A. Siregar; Imani Santriani (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2022)
The development of tourism in the future will face increasingly fierce competition in both marketing and tourismproduct development. A place that can be said as a tourist destination is certainly supported by various things, one ofwhich is a tourist attraction and promotion on social media as an information tool. A tourist attraction is aninteresting and worthy tourist place to visit. In addition to tourist attractions, promotions on social media can attractthe attention of customers to visit tourist attractions. However, Tourist Attractions and Instagram Promotionsrequire a maximum strategy so that the information provided can be given correctly and maximally. The RanchCisarua experienced a decrease in visitors in 2021 by 35 percent and the management of Instagram social media isstill not optimal. Based on this, the purpose of this study was to determine the effect of tourist attraction andInstagram promotion on the decision to visit The Ranch Cisarua. This research is a type of quantitative research. Theresearch was conducted at The Ranch Cisarua. The sampling technique is non-probability sampling with purposivesampling type. The number of samples of 100 people was taken from the total population of Instagram followers@theranchcisarua as many as 11,300 people. Data collection techniques using questionnaires and observation. Theresults of data analysis and it is known that there is an influence of tourist attraction and Instagram promotion onthe decision to visit The Ranch Cisarua by 64 percent. Meanwhile, 36 percent is influenced by other variables notexamined in this study.Keywords: Tourist Attractions, Visiting Decisions, Instagram Promotions, Publicity.